2017
DOI: 10.1002/jor.23614
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of rifampicin: A technique to preserve the mechanical properties of bone cement

Abstract: Two-stage exchange with antibiotic-loaded bone cement spacers remains the gold standard for chronic periprosthetic joint infection (PJI). Rifampicin is highly efficient on stationary-phase staphylococci in biofilm; however, its addition to PMMA to manufacture spacers prevents polymerization and reduces mechanical properties. Isolation of rifampicin during polymerization by microencapsulation could allow manufacturing rifampicin-loaded bone cement maintaining elution and mechanical properties. Microcapsules of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Rifampicin (RFP) is effective against staphylococcal infections and efficient for treatment at any bacterial growth stage (i.e. exponential, stationary, intracellular) (Frippiat et al, 2004;Sanz-Ruiz et al, 2017;Trampuz and Widmer, 2006). Furthermore, RFP is also one of the most effective first-line drugs for the treatment of tuberculosis and its bone-related effects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Rifampicin (RFP) is effective against staphylococcal infections and efficient for treatment at any bacterial growth stage (i.e. exponential, stationary, intracellular) (Frippiat et al, 2004;Sanz-Ruiz et al, 2017;Trampuz and Widmer, 2006). Furthermore, RFP is also one of the most effective first-line drugs for the treatment of tuberculosis and its bone-related effects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Most antifungal drugs only effectively inhibit planktonic fungal cells during the exponential growth phase but have little effect on biofilms. Currently used antibiotics, including gentamicin (Scott and Higham, 2003), rifampicin (Sanz-Ruiz et al, 2018), and clindamycin (Neut et al, 2005;Ooi et al, 2017), have been applied on devices to cope with medical device HAIs, but the consequent emergence of antibiotic-resistance bacteria raise more questions (Thornes et al, 2002). Other antimicrobial agents, such as metals (Antonelli et al, 2012) and bacteriophages (Lu and Koeris, 2011), have been tested for their ability to remove biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is the encapsulation of rifampin before it is mixed with the cement. Sanz-Ruiz et al 33 encapsulated rifampin and reported effective elution of the antibiotic while preserving the mechanical properties of PMMA. Similar results were reported with the use of rifampin-filled cyclodextrin (CD) microparticles.…”
Section: Discussionmentioning
confidence: 99%